DEVELOPMENT AND IMPLEMENTATION OF COMPREHENSIVE TREATMENT AND REHABILITATION APPROACHES FOR PAIN DYSFUNCTION OF THE CROP IN PATIENTS WITH JAW FRACTURES - Mamedov Izmir; Maryam Magomedovna Malachilova; Iraiganat Gamidovna Gadisova; Dzhamilya Sharabutinovna Dadaeva (TADQIQOTLAR, 2026)
Annotation. The work presents a study aimed at improving the effectiveness of treatment for temporomandibular joint pain disorder (TMJ) in patients with mandibular fractures. The relevance of the topic is due to the high prevalence of injuries to the maxillofacial  region  and  the  significant  percentage  of  post-traumatic  functional disorders  of  the  maxillofacial  region,  leading  to  pain  syndrome,  limitation  of mandibular movement, and a decrease in the quality of life of patients.